The Effect of the Internet Banking on Customer Loyalty: A Study among Malaysian Banks - Saleh, Abdulbaset Mohamed I. (2009)
The banking services have been dynamic during the last decade due to the advent of the Internet in banking sector. One of the most vital challenges of the Internet as a service delivery channel is providing and maintaining service quality. Service quality is an input of customer trust which becomes satisfaction and lead to loyalty as an output. Customer loyalty is a concern of any organizations as well as banking sectors. The purpose of this research was to gain better understanding of the impact of the Internet on customer loyalty in Malaysian banks. Four research questions have been formulated to achieve the purpose. Based on detailed literature review, a frame of reference was developed which helped to answer research questions and guide to data collection. A quantitative research approach was used to get better understanding of this issue. Empirical data were collected through questionnaires with the research questions and the frame of reference. Finally, in the last chapter findings and conclusions were drawn by answering research questions. In the research it was found that all the banks interviewed seem to have the same description, motivation and an underlining objective of customer loyalty and the Internet has affected from two different directions which are made up of both positive and negatives sides on customer loyalty creation by theses banks. The Internet has become more powerful media of providing bank services. Banks use the Internet as a new distribution channel for their products and services. The Internet facilitates home banking services which is becoming more popular in recent time. Another most important finding of this study, from both banks, is service quality which form an integral part of loyalty creation.